DEVELOPING WEB MAPPING APPLICATION USING ARCGIS SERVER WEB APPLICATION DEVELOPMEN FRAMEWORK (ADF) FOR GEOSPATIAL DATA GENERATED DURING REHABILITATION AND RECONSTRUCTION PROCESS OF POST-TSUNAMI 2004 DISASTER IN ACEH - Nizamuddin Nizamuddin (Universitas Syiah Kuala, 2013)
ESRI ArcGIS Server is equipped with ArcGIS Server Web Application Development Framework (ADF) and ArcGIS Web Controls integration for Visual Studio.NET. Both the ArcGIS Server Manager for .NET and ArcGIS Web Controls can be easily utilized for developing the ASP.NET based ESRI Web mapping application. In this study we implemented both tools for developing the ASP.NET based ESRI Web mapping application for geospatial data generated dring rehabilitation and reconstruction process of post-tsunami 2004 disaster in Aceh province. Rehabilitation and reconstruction process has produced a tremendous amount of geospatial data. This method was chosen in this study because in the process of developing a web mapping application, one can easily and quickly create Mapping Services of huge geospatial data and also develop Web mapping application without writing any code. However, when utilizing Visual Studio.NET 2008, one needs to have some coding ability.